The Effects of Genre Based Approach and Process Approach on EFL Writing Class - Yuni Putri Utami,; Budyi Suswanto,; Nurul Fadhilah, (Technium Social Sciences Journal, 2023)
Indonesian students learn English as a Foreign Language (EFL). Indonesian students who are second language users (L2 learners) have limited knowledge of frequently used words compared to first language users (L1 learners) and native English speakers. EFL students made more mistakes and errors in EFL writing classes due to limited vocabulary. A frequent word is a single word in the first three frequency levels of the 1000 words. To fill this gap, this study aimed to examine the effectiveness of a genre-based approach (GBA) and a process approach to writing (PAW) on student writing skills. In this study, a quasi-experimental study design was applied in the form of a pre-test and post-test control group design. As a sample for this study, two classes of 3rd semester undergraduate students from the Faculty of Economics and Business in Sumenep, East Java, Indonesia were randomly selected. Seventy students participated in the study, of which 35 students in the experimental group received the GBA and another 35 students in the control group received the process approach to writing. Data were analysed using independent and dependent (paired) sample t-tests. The resulting findings showed that: 1) There was a significant difference in post-test scores between students taught using a genre-based approach and those taught using a process approach to writing. 2) Adopting a genre-based writing approach or a process approach has had a big impact. This study shows that the genre-based approach contributes more than the writing approach. In conclusion, the GBA or PAW was effective in teaching English writing skills.